Candida arteritis in kidney transplant recipients: case report and review of the literature. Issue 3 (26th May 2015) - Dębska‐Ślizień, A.; Chrobak, Ł.; Bzoma, B.; Perkowska, A.; Zadrożny, D.; Chamienia, A.; Kostro, J.; Milecka, A.; Bronk, M.; Śledziński, Z.; Rutkowski, B.
Abstract Multi‐organ procurement is a risk factor for contamination of preservation fluid with intestinal flora including fungi (e.g., Candida). Transmission of fungal species to the graft vessel can cause mycotic arteritis. This is a very rare but life‐threatening complication of renal transplantation. We present 2 cases of renal transplant recipients from the same multi‐organ donor. Both recipients suffered from severe hemorrhages from renal graft anastomosis and renal artery pseudoaneurysm due to Candida albicans arteritis (CAA). The culture of the preservation fluid revealed growth of Escherichia coli, but neither preservation fluid nor multiple routine blood cultures performed before hemorrhagic complications revealed fungal growth (media non‐selective for fungal growth were applied). The first recipient suffered from sudden severe hemorrhage in the area of graft anastomosis on day 10 post surgery (without any preceding clinical or radiological symptoms). This led to urgent surgery and graftectomy, which was complicated by cardio‐respiratory arrest with resuscitation in the operating room; despite resuscitation, irreversible brain damage, and subsequent death occurred in the intensive care unit (ICU) 2 weeks later (on day 24 after transplantation). The second patient underwent urgent vascular surgery on day 22 (after transplantation), because of hemorrhage from a pseudoaneurysm of the graft artery. She required repeated vascular operations, extended antimicrobial and antifungal therapy, and ICU monitoring and, despite these interventions, she died on day 80 after transplantation as a result of Pseudomonas aeruginosa sepsis. Arteritis of the renal artery in both patients was caused by C. albicans. This was confirmed by histopathology: infiltration of renal artery with budding yeast forming pseudohyphae (Case 1), and the presence of C. albicans in the culture of the renal artery and surrounding tissue (Case 2). We conclude that organ preservation solution should be cultured with use of media selective for fungal growth. As soon as the positive culture is detected, appropriate measures protecting patients against CAA should be undertaken.